2017
DOI: 10.13031/aea.11876
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Field Characterization of the Sifang Mini Rice Combine Harvester

Abstract: Abstract. Performance of a Sifang mini rice combine, originally developed in China, was evaluated under local farmer field conditions in Benin. Results from field evaluation show that the combine worked satisfactorily on less dense rice fields with minimal weeds at grain moisture contents between 19.1% and 20.1% w.b. on soils with moisture content from 23% to 33% d.b. while causing no significant changes to soil physical properties. With harvesting speed ranging from 0.8 to 4.5 km/h, the harvester had a field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Several rice varieties have been developed for different rice production systems. In addition, good practices (agronomic and postharvest) including mechanization options are also being developed or adapted to increase the quantity and quality of locally produced rice (Amponsah, Addo, Dzisi, Moreira, & Ndindeng, ; Ndindeng et al., ; Saito et al., ). It is worth noting that most technologies have not reached most end‐users to produce the desired impact.…”
Section: Introductionmentioning
confidence: 99%
“…Several rice varieties have been developed for different rice production systems. In addition, good practices (agronomic and postharvest) including mechanization options are also being developed or adapted to increase the quantity and quality of locally produced rice (Amponsah, Addo, Dzisi, Moreira, & Ndindeng, ; Ndindeng et al., ; Saito et al., ). It is worth noting that most technologies have not reached most end‐users to produce the desired impact.…”
Section: Introductionmentioning
confidence: 99%
“…Paddy loss could be saved 4.47% using combine harvester over manual harvesting. Amponsah et al (2017) mentioned grain loss using combine ranging from 1.43% to 4.43% and 1.85% to 5.6% for the IR841 and Nerica L20 rice varieties, respectively. Kannan et al (2013) reported similar post-harvest loss of paddy.…”
Section: Loss Of Paddy Saved Using Mechanical Harvestingmentioning
confidence: 97%
“…Although it was expected that parboiling will result in the control of fungi and mycotoxin in milled parboiled rice, Kaushik (2013) In SSA, domestic milled rice (white and parboiled) is mostly of low quality and characterized by low head rice, high proportions of impurities, and chalky grains. In addition, both suboptimal pre-and postharvest practices are commonly used (Amponsah et al, 2017;Mapiemfu et al, 2017;Ndindeng et al, 2015). This rice is mostly sold in bulk or stored in plastic woven bags, jute bags, or bulk storage systems.…”
Section: Modeling the Effect Of Temperature Relative Humidity Gramentioning
confidence: 99%
“…In each of these segments, the physicochemical, nutritional, and economic value of the milled rice can be reduced by microbial invasions especially in the humid tropics (Gummert, Balingbing, Barry, & Estevez, ). Farmer's practices and environmental conditions that enhance insect propagation, microbial proliferation, and mycotoxin production during these production and processing stages include the following: the use of disease‐infected seeds, the nonelimination of disease‐infected plants during production, poor harvesting, threshing, drying, parboiling, and milling methods favoring grain damage and/or their contamination (Amponsah, Addo, Dzisi, Moreira, & Ndindeng, ; Mapiemfu et al, ; Ndindeng et al, ) and storage of grains in systems that favor the re‐absorption of moisture or expose them to high oxygen levels (Fleurat‐Lessard, ; Magan, Hope, Cairns, & Aldred, ), which promote microbial proliferation. Enormous quality deterioration occurs during storage (Majumder, Bala, Arshad, Haque, & Hossain, ) including mycotoxigenic secretion by contaminants predominantly represented by the genera Aspergillus, Fusarium, and Penicillium (Makun, Dutton, Njobeh, Mwanza, & Kabiru, ; Makun, Gbodi, Akanya, Salako, & Ogbadu, ; Reddy, Reddy, & Muralidharan, ).…”
Section: Introductionmentioning
confidence: 99%